Health economic impact of moderate-to-severe chronic pain associated with osteoarthritis in England: a retrospective analysis of linked primary and secondary care data - David Walsh; Roger Knaggs; Christoph Lohan; Robert Wood; Alastair J Dickson; Theo Tritton; Greg Coates; Peter Clewes; Hannah Stevenson (BMJ Open, 2023)
Objective Despite the prevalence of osteoarthritis (OA) in England, few studies have examined the health economic impact of chronic pain associated with OA. The aim of this study was to compare outcomes in patients with moderate-to-severe chronic pain associated with OA and matched controls without known OA.Design Retrospective, longitudinal, observational cohort study.Setting Electronic records extracted from the Clinical Practice Research Datalink GOLD primary care database linked to Hospital Episode Statistics (HES) data set.Participants Patients (cases; n=5931) ≥18 years and with existing diagnosis of OA and moderate-to-severe pain associated with their OA, and controls matched on age, sex, comorbidity burden, general practitioner (GP) practice and availability of HES data.Interventions None.Primary and secondary outcome measures Total healthcare resource use (HCRU) and direct healthcare costs during 0–6, 0–12, 0–24 and 0–36 months of follow-up. Secondary outcomes measures included pharmacological management and time to total joint replacement.Results Patients with moderate-to-severe chronic pain associated with OA used significantly more healthcare services versus matched controls, reflected by higher HCRU and significantly higher direct costs. During the first 12 months’ follow-up, cases had significantly more GP consultations, outpatient attendances, emergency department visits and inpatient stays than matched controls (all p<0.0001). Total mean costs incurred by cases during 0–12 months’ follow-up were five times higher in cases versus controls (mean (SD): £4199 (£3966) vs £781 (£2073), respectively). Extensive cycling through pharmacological therapies was observed; among cases, 2040 (34.4%), 1340 (22.6%), 841 (14.2%), 459 (7.7%) and 706 (11.9%) received 1–5, 6–10, 11–15, 16–20 and >20 lines of therapy, respectively.Conclusions This wide-ranging, longitudinal, observational study of real-world primary and secondary care data demonstrates the impact of moderate-to-severe chronic pain associated with OA in patients compared with matched controls. Further studies are required to fully quantify the health economic burden of moderate-to-severe pain associated with OA.